`It makes sense and it works': Maternity care providers' perspectives on the feasibility of a group antenatal care model (Pregnancy Circles). (November 2018) - Hunter, Louise; Da Motta, Giordana; McCourt, Christine; Wiseman, Octavia; Rayment, Juliet; Haora, Penny; Wiggins, Meg; Harden, Angela
Highlights: Dissatisfaction with current care provision was reported by commissioners, managers and midwives. Within a system that did not support this, Pregnancy Circles enabled midwives to provide antenatal continuity of carer. Midwives in this setting experienced group care as a safe and fulfilling way to provide care. Midwives need support and a facilitative practice environment in which to develop new ways of working. Abstract: Aim: To test the feasibility of introducing a group antenatal care initiative ( Pregnancy Circles) in an area with high levels of social deprivation and cultural diversity by exploring the views and experiences of midwives and other maternity care providers in the locality before and after the implementation of a test run of the group model. Design: (i) Pre-implementation semi-structured interviews with local stakeholders. (ii) Post-implementation informal and semi-structured interviews and a reflective workshop with facilitating midwives, and semi-structured interviews with maternity managers and commissioners. Data were organised around three core themes of organisational readiness, the acceptability of the model, and its impact on midwifery practice, and analyzed thematically. Setting: A large inner-city National Health Service Trust in the United Kingdom. Participants: Sixteen stakeholders were interviewed prior to, and ten after, the group model was implemented. Feedback was also obtained from a further nine midwives and one student midwife who facilitated the Pregnancy Circles . Intervention: Four Pregnancy Circles in community settings. Women with pregnancies of similar gestation were brought together for antenatal care incorporating information sharing and peer support. Women undertook their own blood pressure and urine checks, and had brief individual midwifery checks in the group space. Findings: Dissatisfaction with current practice fuelled organisational readiness and the intervention was both possible and acceptable in the host setting. A perceived lack of privacy in a group setting, the ramifications of devolving blood pressure and urine checks to women, and the involvement of partners in sessions were identified as sticking points. Facilitating midwives need to be adequately supported and trained in group facilitation. Midwives derived accomplishment and job satisfaction from working in this way, and considered that it empowered women and enhanced care. Key conclusions: Participants reported widespread dissatisfaction with current care provision. Pregnancy Circles were experienced as a safe environment in which to provide care, and one that enabled midwives to build meaningful relationships with women. Implications for practice: Pre-registration education inadequately prepared midwives for group care. Addressing sticking points and securing management support for Pregnancy Circles is vital to sustain participation in this model of care.